Toward an efficient stress transfer with a fully connected hybrid network from epoxy, oxidized UHMWPE fibers, and silane surface modified silicon carbide nanoparticles. Issue 1 (8th October 2020) - Belgacemi, Raouf; Derradji, Mehdi; Trache, Djalal; Zegaoui, Abdeldjalil; Mehelli, Oussama
Abstract: In this work, a new high‐performance hybrid material was designed targeting excellent static and dynamic mechanical properties. To achieve this goal, the hybrid constituents, namely the ultra‐high molecular weight polyethylene fibers and silicon carbide nanoparticles, were respectively, surface modified to graft the proper chemical species in order to maximize the interactions between the reinforcing phases and the epoxy matrix. The adopted grafting procedures were characterized by vibrational and morphological analyses. The generation a fully connected network resulted in consequent ameliorations in the mechanical and thermomechanical properties. Meanwhile, the effect of various amounts of the treated silicon carbide nanoparticles was also investigated. The finding indicated a gradual improvement in the overall mechanical properties up to 5 wt% for which the tensile strength reached its maximum value of about 477 MPa. The same hybrid materials displayed the remarkable storage modulus of 7.7 GPa at 25°C and a glass transition temperature of about 66°C. The synergistic stress transfer between the constituents was further evidenced by a proper investigation of the sample's fractured surfaces. Overall, the study revealed the great advantage of a fully connected network in developing lightweight and high‐performance materials for exigent applications. Abstract : The present work describes a successful attempt in creating hybrid materials with fully connected constituents. It is well‐known that in order to obtain high performance hybrid materials a synergistic effect needs to be reached allowing an efficient stress transfer and optimal performances. Thus, in this study the ultra‐high molecular weight polyethylene (UHMWPE) fibers and silicon carbide (SiC) nanoparticles were respectively, surface modified to graft the proper chemical species in order to maximize the interactions between the reinforcing phases and the epoxy matrix.